Vertical Alignment of Liquid Crytals on Polydimethylsiloxane Thin Films - Zheng, Wenjun; Yang, Luhsiang; Lee, Mengchiao (Photonics Letters of Poland, 2011)
Studies on the use of polydimethylsiloxane to align liquid crystals have been carried out. The thin films prepared using the silicon-based elastomer, with a pretty low surface free energy, are found to be capable of vertically aligning liquid crystals. The pretilt angle of calamitic liquid crystals sandwiched between thin silicon elastomer films was virtually 90 degrees. Liquid crystal devices consisting of elastomer alignment layers can operate in the in-plane-switch mode. Full text: PDF References: E. Lueder, Liquid Crystal Displays-Addressing Schemes and Electro-Optical Effects (Chichester, John Wiley & Sons 2001) J. Glueck, (PhD Thesis, University of Stuttgart 1995) DisplaySearch, Quarterly Wide Viewing Angle Technology Report (2010) [DirectLink] C.M. Knobler, "A microstamp of approval", Nature 369, 15 (1994) [CrossRef] D. Qin, Y. Xia, G.M. Whitesides, "Rapid prototyping of complex structures with feature sizes larger than 20 ?m", Adv. Mater. 8, 917 (1996) [CrossRef] M. Geissler, Y. Xia, "Patterning: Principles and Some New Developments", Adv. Mater. 16, 1249 (2004) [CrossRef] Y.T. Kim, J.H. Hong, T.Y. Yoon, S.D. Lee, "Pixel-encapsulated flexible displays with a multifunctional elastomer substrate for self-aligning liquid crystals", Appl. Phys. Lett. 88, 263501 (2006) [CrossRef] D.K. Owens, R.C. Wendt, "Estimation of the surface free energy of polymers", J. Appl. Polym. Sci. 13, 1741 (1969) [CrossRef] W. Zheng, C. H. Lu, Y. Yeh, "Effects of Mechanical Rubbing on Surface Tension of Polyimide Thin Films", Jpn. J. Appl. Phys. 47, 1651 (2008) [CrossRef] L.T. Creagh, A.R. Kmetz, "Mechanism of Surface Alignment in Nematic Liquid Crystals", Mol. Cryst. Liq. Cryst. 24, 59 (1973) [CrossRef] F.J. Kahn, C.N. Tayor, H. Schonhorn, "Surface-produced alignment of liquid crystals", Proc. IEEE 61, 823 (1973) [CrossRef] W. Zheng, L. Yang, R.O.C. Patent, 200931140